Overview of Rheumatoid Arthritis-Associated Interstitial Lung Disease and Its Treatment - Pugashetti, Janelle Vu; Lee, Joyce S. (Seminars in Respiratory and Critical Care Medicine, 2024)
Interstitial lung disease (ILD) is a common pulmonary complication of rheumatoid arthritis (RA), causing significant morbidity and mortality. Optimal treatment for RA-ILD is not yet well defined. Reliable prognostic indicators are largely byproducts of prior ILD progression, including low or decreasing forced vital capacity and extensive or worsening fibrosis on imaging. In the absence of validated tools to predict treatment response, decisions about whether to initiate or augment treatment are instead based on clinical judgment. In general, treatment should be initiated in patients who are symptomatic, progressing, or at high risk of poor outcomes. Retrospective data suggest that mycophenolate mofetil, azathioprine, and rituximab are likely effective therapies for RA-ILD. Abatacept is also emerging as a potential first-line treatment option for patients with RA-ILD. Further, recent data demonstrate that immunosuppression may be beneficial even in patients with a usual interstitial pneumonia (UIP) pattern on imaging, suggesting that immunosuppression should be considered irrespective of imaging pattern. Recent randomized controlled trials have shown that antifibrotic medications, such as nintedanib and likely pirfenidone, slow forced vital capacity decline in RA-ILD. Consideration can be given to antifibrotic initiation in patients progressing despite immunosuppression, particularly in patients with a UIP pattern. Future research directions include developing tools to predict which patients will remain stable from patients who will progress, discriminating patients who will respond to treatment from nonresponders, and developing algorithms for starting immunosuppression, antifibrotics, or both as first-line therapies.
Keywords: rheumatoid arthritis; interstitial lung disease; usual interstitial pneumonia; treatment; management; mycophenolate; azathioprine; rituximab; abatacept